Mapa conceitual, um gênero textual escolar: uma proposta de retextualização de textos didáticos de história - Yoshimoto, Elton Mitio; Yoshimoto, Graziele Maria Freire; Santos, Givan José Ferreira Dos; Oliveira, Marilu Martens [UNESP] (Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira, 2016)
We present here an experience report on a retextualization practice of didactic texts on History based on production of conceptual maps. This research was carried out with students of the 6th grade of the elementary school II, at the state school located in the city of Cambé (Paraná state). In the study, we investigated whether new knowledge was built by students as from the production of such conceptual maps. We supported our study on the Theory of Meaningful Learning, the Theory of Text Genre and the procedural approach to text production. Results indicate that by retextualizing didactic texts, students established new relationships and gave a new meaning to the contents studied, compared to their previous knowledge about the subject. We also observed that the collaborative and dialogical practice was essential to the construction of new knowledge for the relationship they established in the diagrams produced. We expect to contribute to the debates involving the production of conceptual map as a possibility of retextualization and as an important academic genre to develop a meaningful learning.

Apresenta-se um relato de experiência de uma prática de retextualização de textos didáticos de história mediante a produção de mapas conceituais. O estudo é desenvolvido com alunos do 6º ano do ensino fundamental II, em escola estadual localizada no município de Cambé-Paraná, e investiga se novos conhecimentos foram construídos por eles em virtude da produção desses mapas. Os resultados indicam que os alunos, ao retextualizarem textos, estabeleceram novas relações e ressignificaram os conteúdos estudados, se comparados aos seus conhecimentos prévios sobre o tema. Observa-se que a prática colaborativa e dialógica foi fundamental para a construção de novos conhecimentos com base na relação que estabeleceram nos diagramas produzidos. Espera-se com esse relato contribuir para os debates que envolvem a produção do mapa conceitual enquanto uma possibilidade de retextualização e como um gênero textual escolar produtivo no desenvolvimento de uma aprendizagem significativa.
Conceptual map, an academic textual genre: a proposal for retextualization of didactic texts on History
Keywords: conceptual map; textual genre; retextualization; meaningful learning; History teaching; mapa conceitual; gênero textual; retextualização; aprendizagem significativa; ensino de história